VOICES OF FLOR DA SERRA RESETTLEMENT: MEMORY, IDENTITY AND - Medina, Maria de Fatima Rocha; Silva, Marinalva do Rego Barros [UNESP]; Amaral, Leila Dias Pereira do; Storniolo, Liliane Scarpin da Silva [UNESP]; Sousa, Albetania Pessoa de (Fundacao Univ Tocantins, 2022)
This work in the area of Oral Poetics focuses on narratives by residents of the Flor da Serra resettlement. They were displaced from various parts of the state because of the Luis Eduardo Magalhaes hydroelectric on the Tocantins River. The objective was to investigate narratives and/or other traditional cultural references that residents of the Flor da Serra resettlement practiced before the compulsory displacement and the memories they have of the process of formation of the social group at the new space. Qualitatively, had approach a combination of story life, real-life observation and semi-structured interviews. The narratives of adult and elderly interpreters (residents), who agreed to participate in the project after signing the Free and Informed Consent Term (FICT), were registered. The data gathering procedure was carried out on site with the use of cell phone recorders, in addition to notes in a field notebook. After the data gathering, the audios were transcribed/transposed from orality to writing. Residents of Flor da Serra expressed common aspects, such as a positive assessment in relation to the land of origin. When talking about the beginning of the resettlement, most lamented the lack of water and unproductive land; the lessons learned around the creation of the association; and they also revealed homesickness for people who stayed or were moved to other places.
Keywords: Flor da Serra Resettlement; Remembrance; Narratives; Cultural Practices